2014
DOI: 10.1007/s10549-014-2903-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in biological features of breast cancer between Caucasian (Italian) and African (Tanzanian) populations

Abstract: Information on hormone receptor and human epidermal growth factor receptor-2 (HER2) expression in breast cancer is acknowledged as mandatory for prognostic stratification and treatment planning. Data on the biological features of African breast cancers are poor. We decided to compare histopathological and biomolecular characteristics (estrogen and progesterone receptor—ER, PgR, and HER2) of Tanzanian and Italian breast cancers. Differences in proliferating index and androgen receptor (AR) expression in triple-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 20 publications
7
45
1
Order By: Relevance
“…The same trend has been observed in Native Africans. At the same time, as reported in our previous paper, [27] Tanzanian and Italian BCs present different histopathological and biomolecular characteristics: African patients have a higher frequency of negative prognostic markers, such as poor differentiation grade, ER-negative status, high proliferation index or advanced stage at diagnosis [28]. …”
Section: Introductionmentioning
confidence: 57%
“…The same trend has been observed in Native Africans. At the same time, as reported in our previous paper, [27] Tanzanian and Italian BCs present different histopathological and biomolecular characteristics: African patients have a higher frequency of negative prognostic markers, such as poor differentiation grade, ER-negative status, high proliferation index or advanced stage at diagnosis [28]. …”
Section: Introductionmentioning
confidence: 57%
“…A former survey conducted to identify potential molecular differences between breast cancers in Europe and the Middle East demonstrated that the incidence of low-grade disease was 14 times lower in Saudi than Swiss women suggesting differences in genetic susceptibility [25]. Further research from developing countries showed that the African Tanzanian women had poorly differentiated breast cancers that expressed higher ER and/or PR negative contents and presented at significantly late stages compared to the Caucasian Italian women [35]. Identical findings were presented in a descriptive survey that analyzed the pathological behavior of breast cancer among Ghanaian Sub-Saharan African women versus the Norwegian coordinate [36].…”
Section: Discussionmentioning
confidence: 99%
“…In Sub-Saharan Africa, the incidence of breast cancer ranged from 15 to 53 per 100,000 women, which are lower than those in industrialized countries [2]. However, the cancer burden reported for sub-Saharan Africa may be underestimated due to the lack or insufficient awareness, a lack of appropriate diagnosis, poor access to care, limitations in the technical workforce and infrastructure, and low quality of cancer data systems compared to those in high resource countries [3] [4]. In Guinea, the incidence of breast cancer is estimated at 14.5 new cases per 100,000 [5] and breast cancer accounts for over 26% of all cancers at our surgical oncology unit [6].…”
Section: Introductionmentioning
confidence: 99%